Wide variation in organisation and clinical practice of paediatric intestinal failure teams: an international survey. Issue 6 (December 2018) - Neelis, Esther; de Koning, Barbara; van Winckel, Myriam; Tabbers, Merit; Hill, Susan; Hulst, Jessie
Summary: Background & aims: We aimed to assess the current organisation and clinical practice of teams treating children with intestinal failure (IF) across Europe and compare the results with the current guideline. Methods: A two-part online survey was sent to all the major European specialist IF services. The first part concerned general information about the team and patients monitored. The second part concerned important care topics such as vascular access and monitoring of complications. No patient identifiers were collected. Results: Seventy-three respondents completed the first part, representing 61 teams in 20 countries. The median number of children on parenteral nutrition (PN) at home per team was 15 (range 1–125). Teams consisted of the following members: paediatric gastroenterologist (present in 100% of the teams), dietitian (95%), specialist nurse (92%), paediatric surgeon (89%), pharmacist (82%), psychologist (66%), social worker (62%), speech therapist (48%), physiotherapist (38%), general paediatrician (33%). The second part was completed by 67/73 respondents (59/61 teams). Vascular access care was comparable with the guideline. Somatostatin analogues were prescribed by 14% of the IF teams and probiotics by 44% of the teams. Prophylactic anticoagulation was used by 46% of the teams. In 81% of the teams a multicomponent lipid emulsion containing fish oil was routinely used. Bone densitometry was regularly performed in 75% of teams, but never performed in 19%. Conclusions: In conclusion, there is a wide diversity of composition of IF teams and their number of patients treated. Overall, there is good compliance to the current guideline. Clinical practice that varied most was the standard use of medication such as probiotics and somatostatin analogues, and standard monitoring of long-term complications. Experience regarding specific treatment options should be shared. Moreover, international agreement on standards of care with focus on implementation of the guideline is needed to optimise care and improve outcomes of children with IF.